Kinerja ASN Dalam Menghadapi Refocusing Anggaran Di Masa Pandemi Covid-19 - Kartika, Ray Septianis (Jurnal Administrasi dan Kebijakan Publik, 2021)
Budget refocusing becomes a problem when program activities cannot be realized according to the target. The effect is to affect the volume of employees to work. Facing this, it is very important to see how ASN can work optimally in the midst of budget constraints. This study looks at the dimensions of qualification, competence, performance and discipline. The purpose of this study is to find out how the performance of ASN in the face of budget refocusing by looking at the four dimensions. The method is descriptive qualitative, the respondents come from elements of the central government and local government which are recorded in the goggle form application. The results of the study were analyzed that the qualification dimension relates between education and class, the competency dimension measures the competence of ASN from their position, the performance dimensions of respondents who already know refocusing information are 66.53% and 62.50% are of the opinion that budget refocusing affects performance, and 81.65 % approve the refocusing policy. The discipline dimension talks about activity planning, independent study and work innovation. The findings of the study are First, ASN continues to carry out activities as usual even though refocusing has been carried out, Second, ASN productivity is shown by budget realization and achievement of fulfilling annual credit scores for researchers, Third General functional officials carry out action plans in dealing with the situation by shifting non-priority activities into activities that are output based. The suggestion is that the first is integrated managerial planning, the second is output-based research. The third is realizing comprehensive work innovation. Thus the achievement of the institution and the target of the institution will be achieved without reducing its usefulness.